Gout and kidney during XVII and XIX centuries - A. Antonello; M. Rippa Bonati; A. D'Angelo; G. Gambaro; L. Calò; L. Bonfante (PAGEPress Publications, 2002)
The authors briefly describe the history of gout, mainly focusing their attention on the renal involvement. They report some works and theories on gout of great ancient physicians, such as Paracelsus, Sydenham, Boerhaave, Van Swieten and Morgagni.